The Dominant Factor Affecting Customer Buying Decisions at Online Retail Stores in Jakarta - Rudy Santosa Sudirga (Sekolah Tinggi Manajemen IPMI, 2021)
Research on the dominant factors affecting customer buying decisions at online retail stores in Jakarta is based on increasing competition in online retail store businesses such as Tokopedia, Bukalapak, Lazada Indonesia, Kaskus, and others. This increase will have a good impact on improving the economy and also increasing the workforce in Indonesia. The author wishes to find out which of the most dominant factors greatly influences customer buying decisions in shopping at retail stores online in Jakarta. The results of respondents who answered the questions were dominated by respondents with a bachelor degree education background, 110 people (55%), with ages ranging between 31 - 40 years, 114 people (57%), and have an income of 11 - 30 million rupiah per month, 121 people (60.50%), and according to the frequent online shopping between 2-3 times per month, 101 people (50.50%). Based on the results of data processing, there are 6 most dominant factors that influence customer buying decisions in shopping at online retail stores in Jakarta. These factors are Variable Attitudes with Estimate value = 1,325, Time and Cost Efficiency Variable with Estimate value = 1,272, Variable Values ​​with Estimate value = 1,243, Family Variable with Estimate value = 1,215, Beliefs Variable with Estimate value = 1,197, Variety of Choices Variable with Estimate value = 1,091.